IDENTIFIKASI KAYU PERAHU KUNA SITUS PUNJULHARJO REMBANG JAWA TENGAH - Widyanto Dwi Nugroho (Balai Arkeologi Yogyakarta, 2009)
Indonesia is a country with a rich maritime history. The finding of ancient wooden ark in Punjulharjo site, Rembang, Central Java that was ascribed to seventh century A.D., was a proof of the growth of the ancient maritime culture. This finding needs some support to find out the origin of the ark. This research was intended to identify the wood species used on board, stringer and dowel part. The identification result was expected to be useful to estimate the origin of the wooden ark.The wood identification process was done by observing the wood anatomy on the board, stringer and the dowel part using loupe and light microscopy. The identification result showed that according to its wood’s characteristic, the board part of the ark was predicted as wood from the family Sapotaceae, genus Palaquium, and species Palaquium spp. (Nyatoh Wood); wood used as stringer part was estimated as wood from the family of Olacaceae, family Scorodocarpus and species Scorodocarpus bornesis (Kulim Wood) and the wood used as dowel part was estimated as wood from the family Myrtaceae, genus Melaleuca and species Melaleuca leucadendron (Cajuput Wood). Based on the natural distribution of species used as component making of the ark, it was estimated that the ark was originated from Indonesian archipelago, specifically Sumatra island, Borneo island or Malay Peninsula.